Alternative Fuel Analysis of Polyethylene Type Plastic Waste Pyrolysis Results - Yeni Ratih Pratiwi; Johan Wayan Dika; Abi Suwito; Muhammad Farid Fajar Sururi (University of Merdeka Malang, 2022)
Plastic waste is a major problem faced by Indonesia, especially in big cities which have a high level of activity and density as well as rapid infrastructure development. To overcome this, environmental experts and scientists from various disciplines have conducted various studies and actions. One alternative for handling plastic waste is to carry out a recycling process (recycle) through pyrolysis. This study aims to analyze liquid fuel from the results of pyrolysis of polyethylene plastic waste. This research is an experimental research with a quantitative approach. The data analysis technique used is data analysis using descriptive techniques. The pyrolysis results obtained consisted of Premium Alternative Fuels producing a density of ± 1060 ml, Kerosene Alternative Fuels producing a density of ± 1480 ml and Alternative Diesel Fuels producing a density of ± 1700 ml.